Cost-Effectiveness Analysis of Antihypertensive Combination Treatment in Chronic Kidney Disease Outpatients with Hypertension - Hadning, Ingenida; Fauztina, Radhwa; Mustofa, Fajar A. (Indonesian Journal of Pharmaceutical Science and Technology, 2025)
The expense of managing CKD patients ranks second highest behind cardiovascular illness, with hypertension being the primary contributor to renal impairment. Maximizing the efficiency of therapeutic expenditures is essential. This study is to evaluate the cost-effectiveness of the combination of amlodipine 10 mg - candesartan 16 mg compared to the combination of candesartan 16 mg - furosemide 40 mg in patients with chronic kidney disease and hypertension. The research employed a non-experimental observational cohort design. The study was performed at both a private and a governmental hospital in Yogyakarta, Indonesia. Data were gathered retroactively using complete sampling. The inclusion criteria comprised outpatients with CKD-hypertension from January 2019 to October 2022, aged 18 years or older, who were undergoing combination therapy. The efficacy of therapy was evaluated by determining the number of samples achieving therapeutic objectives after 2 to 4 weeks. The mean expenditure was derived from monthly antihypertensive costs. The analysis of cost-effectiveness employed the Average Cost-Effectiveness Ratio (ACER) and the Incremental Cost-Effectiveness Ratio (ICER). The study comprised 50 samples, with 51% male participants and 66% aged 60 or older. Amlodipine and candesartan demonstrated superior efficacy (77%) and a reduced average cost of 101,095 IDR. The ACER for amlodipine and candesartan was 1,306 IDR, whereas for furosemide and candesartan it was 1,571 IDR. The amalgamation of amlodipine and candesartan is more economically advantageous than furosemide and candesartan.